Examining Self-Esteem and Socialization Levels of The Students Aged 9-14 Participating in Recreational Activities - Murat Erdoğdu; Muhsin Çınar (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to examine the self-esteem and socialization levels of the students aged 9-14 participating in recreational activities. The population of the study is comprised of 87.814 students attending 5th, 6th, 7th, and 8th grades in public schools in Meram and Selçuklu districts of Konya province in the 2016-2017 academic year. The sample of the study is comprised of 1204 students who were randomly selected from among the research population. In order to reach the predetermined objectives of the study, the Personal Information Form, Self-Esteem Scale, and Socialization Dimension were used. In the analysis of the data, independent group t test, frequency and percentage distributions, one-way variance analysis (ANOVA), post-hoc LSD, T2 tests of Tamhane, and Pearson product moment correlation analyses were used. In the interpretation of the results, the significance level was accepted as p lt; 0.05. Among the findings of the study, it was concluded that the self-esteem levels of female students were higher compared to the males, their self-sufficiency levels increase as their ages progress, and the self-value, self-confidence, achievement and productivity levels of students increase as the parental education level increases. It was also observed that individuals with high socio-economic levels have higher self-esteem scores. In relation to socialization, it was concluded that the socialization levels of female students were higher than male students, and that the socialization levels of the students increased as their parental education and income levels increased. It was concluded that the time spent for recreational activities positively affect self-esteem and socialization levels.